AN EFFECTIVE STRUCTURE FOR STRENGTHENING REINFORCED CONCRETE BEAMS (Academic journal Industrial Machine Building Civil Engineering, 2017)
The study presents a new system of strengthening reinforced concrete beams. The system includes strengthening bars acting on the beam through other strained flexible elements. It operates in a conditionally paradoxical way. It does not compress but strains directly the upper beam zone compressed under the load. Additional flexible elements are made in the form of rods placed obliquely. The study provides the results of determining the most efficient angle of inclination of transverse bars for the external system of strengthening. The paper calculates an efficient angle of inclination of transverse bars that are to unload the beam by the moment reverse in sign of the moment from external load. It also analyzes the results obtained after examining the strengthening by means of a longitudinal-transverse external system and building the diagrams of moments.
Keywords: bars; cross-section; stress; strain; strength; rigidity; span